Unveiling the Role of Hahani (Paternal Aunts) in the VaTsonga Culture of South Africa - Stewart Lee Kugara; Lucky Sethuthuthu Vuma; Tsetselelane Decide Mdhluli (E-Journal of Humanities, Arts and Social Sciences)
Down history, hahani (paternal aunt) played an indispensable role in the family. The paternal aunt was a family figure who was known for skillfully weaving into marital roles, conflict resolution and rituals. She displayed unique flexibility and counseling dexterity to her nieces, nephews and the entire family. Unlike other indigenous groups in Africa, the role of hahani is being downplayed and ignored because of modernity and the growth of families. This indigenous figure in the VaTsonga communities is however a rare gem and her role needs to be preserved before it is abrogated by disuse. This conceptual paper thus adopted the Sankofa Theory to underpin the write-up. To illuminate this subject matter, the paper focused on discussing who the hahani is, her marital counseling role, conflict resolution and leading indigenous rituals in the family from the lived experiences of the authors. In summation, the paper emulates the balanced power of the hahani. The paper argues that the hahani’s existence within the indigenous platforms must be preserved to sustain families of young couples and assist in disciplining and putting into order those who misbehave, and instilling indigenous norms. The paper recommends the usage of local solutions to address local challenges while having a global outlook. In this way, the unique role of hahani must be embraced, ensuring it evolves in an amicable way without distorting and adulterating it. By engaging in the under-researched aspect of VaTsonga culture, the study contributes broadly to gender roles, culture and African family structures thus igniting the impetus of scholarship in this unique field.